Drawing Art with Motivational Interviewing to Solve the Social Skills Problems of Teenagers at SMP 1 Wonosari, Gunungkidul, Yogyakarta - Atifah Hanum Suparjiya; Nurus Sa'adah (Yayasan Ilomata, 2021)
This study aims to look at the effect of drawing art with motivational interviewing in improving adolescent social skills issues at SMP 1 Wonosari. Drawing art as a tool to express problems while motivational interviewing is a step in changing behavior. This research is a quasi-experimental one group pre-test and post-test design, using purposive sampling based on the value of the low category social skills scale with a total of 10 students. Data analysis using SPSS and the Wilcoxon test. Data collection with a scale of social skills, observation, interviews, and documentation. Mean ranks or an average increase of 5.56. The final results using the Wilcoxon test can get the Asymp value. Sig. (2-tailed) of 0.02 <0.05, the hypothesis is accepted meaning that there are differences between social skills from the pre-test and post-test results. It can be concluded that the use of drawing art with motivational interviewing can improve social skills in students in SMP 1 Wonosari.